Legal Consequences If A Debtor Using A Permanent Employee Appointment Decree As Collateral Resigns From Their Workplace - Ayu Saraswati, Nandhina; Hadi, Hernawan (CV. Inara, 2024)
This study aims to analyze the legal consequences if the debtor who uses the guarantee of the Decree of Permanent Employee Appointment resigns from their workplace. This study is normative prescriptive, with a legal approach based on regulations (statute approach) and a conceptual approach. The types and sources of data used are laws and regulations, books on law, scientific journals, scientific articles, and interviews. Data collection through literature studies and the analysis used is description, construction, argumentation, and systematization. The results of this study indicate that debtors who use the guarantee of the Decree of Permanent Employee Appointment resign from their workplace, which results in the guarantee no longer being valid, then online and on-site collection will be conducted until blacklisting in the Financial Services Authority system.